2005
DOI: 10.1080/08880010590921568
|View full text |Cite
|
Sign up to set email alerts
|

GASTRIC ANGIODYSPLASIA IN A CHILD WITH BERNARD-SOULIER SYNDROME: Efficacy of Octreotide in Long-Term Management

Abstract: Gastrointestinal angiodysplasia in association with Bernard-Soulier syndrome has been previously described in adults. The authors report on a 14year-old boy presenting with massive upper gastrointestinal bleeding due to a large gastric angiodysplasia, in whom medical history and laboratory investigations were consistent with Bernard-Soulier syndrome. The vascular lesion was so widespread that surgical or endoscopic therapy was not considered. Therefore, treatment with octreotide, a somatostatin analog, was com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
4
0
2
Order By: Relevance
“…No larger series but numerous case reports have been published so far 17 18. In paediatric liver disease with portal hypertension leading to acute haemorrhage, however, octreotide treatment was shown to be safe and effective 8 19.…”
Section: Discussionmentioning
confidence: 99%
“…No larger series but numerous case reports have been published so far 17 18. In paediatric liver disease with portal hypertension leading to acute haemorrhage, however, octreotide treatment was shown to be safe and effective 8 19.…”
Section: Discussionmentioning
confidence: 99%
“…Octreotide treatment should be considered in patients with refractory gastrointestinal bleeding due to angiodysplasia, in particular in those who need anticoagulant treatment 14. Octerotide has shown a beneficial response in the long-term management of patients with gastrointestinal angiodysplasia 1516…”
Section: Discussionmentioning
confidence: 99%
“…8 However, in pediatric population, experience with octreotide therapy for angiodysplasia is very limited. The only published report on this topic was provided by Kaya et al 12 They reported a 14-year-old boy who presented with upper GI bleeding due to large gastric angiodysplasia in whom octreotide 0.1 mg, subcutaneously, two times per day arrested bleeding within 2 weeks and the effect was maintained for the next 16 months of octreotide therapy. The rationale for the use of octreotide in the bleeding from angiodysplasia is based on its effects on splanchnic circulation.…”
Section: Discussionmentioning
confidence: 99%